Ular Tajir: A Flood-Themed Snakes and Ladders Game for Teaching Flood Mitigation to Elementary School Students - Wedyawati, Nelly; Awang, Imanuel Sairo; Fina, Efiana (Profesi Pendidikan Dasar, 2024)
This study addresses the urgent need for innovative educational tools to enhance flood disaster mitigation literacy among elementary students. We developed Ular Tajir, a Snakes and Ladders-based game, to improve students’ understanding of mitigation strategies and learning outcomes. Employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and a quasi-experimental design, the research involved 124 purposively sampled fourth-grade students in Sintang, West Kalimantan. Data were collected through questionnaires, knowledge assessments, and documentation. Results demonstrated three key outcomes: (1) High feasibility scores from expert validations (97% from media experts, 95% from material experts), confirming the tool’s readiness for educational use; (2) Statistically significant improvements in students’ mitigation comprehension (p = 0.000 < 0.05) across both limited and large-scale trials; and (3) Progressive enhancement of learning outcomes, with peak performance observed during the second trial session. The findings underscore the efficacy of Ular Tajir as an engaging, play-based pedagogical tool for disaster education. This study advocates for integrating interactive, game-driven approaches into curricula to foster both conceptual mastery and practical preparedness in flood-prone communities